Implementasi Prinsip Akuntansi Syariah dalam Upaya Menghindari Praktik Riba terhadap Transaksi Pinjam Meminjam - Windi Anggriyani; Rayyan Firdaus (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to analyze how to implement the principles of Islamic accounting in an effort to avoid usury practices in borrowing and lending transactions in financial institutions. In the world of Islamic finance, it is explained that usury is not permitted because it is something that is forbidden in Islam. This type of research uses a descriptive qualitative approach with a case study methodology on several Islamic financial institutions in Indonesia. Data was collected through interviews, observations, and document analysis. Research findings indicate that the proper and accurate application of Islamic accounting principles can ensure that borrowing and lending transactions conducted within Islamic financial institutions are free from usury practices. Islamic financial institutions tend to implement financing schemes such as murabaha, mudarabah, and musharakah. Furthermore, transparent financial reports that comply with Islamic principles are also key to avoiding usury practices. This research also identifies several challenges faced by Islamic financial institutions in implementing Islamic accounting principles, including the lack of human resources with competent understanding in this field.